Multi‐Fidelity High‐Throughput Optimization of Electrical Conductivity in P3HT‐CNT Composites. (24th June 2021) - Bash, Daniil; Cai, Yongqiang; Chellappan, Vijila; Wong, Swee Liang; Yang, Xu; Kumar, Pawan; Tan, Jin Da; Abutaha, Anas; Cheng, Jayce JW; Lim, Yee‐Fun; Tian, Siyu Isaac Parker; Ren, Zekun; et al.
Abstract: Combining high‐throughput experiments with machine learning accelerates materials and process optimization toward user‐specified target properties. In this study, a rapid machine learning‐driven automated flow mixing setup with a high‐throughput drop‐casting system is introduced for thin film preparation, followed by fast characterization of proxy optical and target electrical properties that completes one cycle of learning with 160 unique samples in a single day, a > 10×  improvement relative to quantified, manual‐controlled baseline. Regio‐regular poly‐3‐hexylthiophene is combined with various types of carbon nanotubes, to identify the optimum composition and synthesis conditions to realize electrical conductivities as high as state‐of‐the‐art 1000 S cm −1 . The results are subsequently verified and explained using offline high‐fidelity experiments. Graph‐based model selection strategies with classical regression that optimize among multi‐fidelity noisy input‐output measurements are introduced. These strategies present a robust machine‐learning driven high‐throughput experimental scheme that can be effectively applied to understand, optimize, and design new materials and composites. Abstract : A graph‐based regressor and optimizer for high‐throughput multi‐fidelity, noisy experiments that designs electronically conducting composites is presented. An automated flow mixing and drop‐casting setup for P3HT‐CNT thin film preparation, followed by rapid characterization of optical and electrical properties of 160 unique samples per day, a >10× improvement relative to baseline, realizing electrical conductivities as high as ≈1000 S cm −1 is presented.